Comparative analysis of petal phytoconstituents reveals insights into the characteristics of an under-reported edible old rose variety native to Chongqing, China - Chan Xu; Yuan Chen; Zongli Hu; Qiaoli Xie; Hang Guo; Shibing Tian; Guoping Chen (Heliyon)
Chongqing Old Rose is an ancient edible rose variety native to Chongqing, China, but is under-reported. Further evidence is required to fully establish its potential benefits. The complete metabolic profiles were examined for comparative analysis between the Old Rose and three rose cultivars. The results showed that the pathways of flavonoid biosynthesis, monoterpenoid biosynthesis, and phenylalanine metabolism were significantly enriched in Old Rose. The predominant anthocyanins in Old Rose were cyanidin and peonidin, which may contribute to flower coloration and indicate the antioxidant potential of this plant. Additionally, this plant was rich in aromatic compounds and terpenoids such as 2-phenylethanol, linalool, geraniol, and caryophyllene α-oxide, indicating that it has a natural basis for extracting essential oil. Moreover, the presence of some active phytoconstituents, such as phenols, steroids, and alkaloids, also suggests its potential for edible and medicinal applications besides flavonoids and terpenoids.